The in vitro MIMIC® platform reflects age-associated changes in immunological responses after influenza vaccination. Issue 41 (4th October 2017) - Dauner, Allison; Agrawal, Pankaj; Salvatico, Jose; Tapia, Tenekua; Dhir, Vipra; Shaik, S. Farzana; Drake, Donald R.; Byers, Anthony M.
Highlights: MIMIC® sys tem is a fully human in vitro model for testing vaccine immunogenicity. In vitro MIMIC® recapitulates in vivo flu-specific immune responses in same cohort. MIMIC® system shows reduced flu-specific B and T cell responses in elderly donors. MIMIC® system reflects the role of donor-intrinsic factors on the immune response. Abstract: Increasing research and development costs coupled with growing concerns over healthcare expenditures necessitate the generation of pre-clinical testing models better able to predict the efficacy of vaccines, drugs and biologics. An ideal system for evaluating vaccine immunogenicity will not only be reliable but also physiologically relevant, able to be influenced by immunomodulatory characteristics such as age or previous exposure to pathogens. We have previously described a fully autologous human cell-based MIMIC® (Modular IMmune In vitro Construct) platform which enables the evaluation of innate and adaptive immunity in vitro, including naïve and recall responses. Here, we establish the ability of this module to display reduced antibody production and T cell activation upon in vitro influenza vaccination of cells from elderly adults. In the MIMIC® system, we observe a 2.7–4.2-fold reduction in strain-specific IgG production to seasonal trivalent influenza vaccine (TIV) in the elderly when compared to adults, as well as an age-dependent decline in the generation of functional antibodies. A parallel decline in IgG production with increasing age was detected via short-term ex vivo stimulation of B cells after in vivo TIV vaccination in the same cohort. Using MIMIC®, we also detect a reduction in the number but not proportion of TIV-specific multifunctional CD154 + IFNγ + IL-2 + TNFα + CD4 + T cells in elderly adults. Inefficient induction of multifunctional helper T cells with TIV stimulation in MIMIC® despite a normalized number of initial CD4 + T cells suggests a possible mechanism for an impaired anti-TIV IgG response in elderly adults. The ability of the MIMIC® system to recapitulate differential age-associated responses in vitro provides a dynamic platform for the testing of vaccine candidates and vaccine enhancement strategies in a fully human model including the ability to interrogate specific populations, such as elderly adults.